Literature, Science, and a New Humanities - Gottschall, J. author. aut Link
XVI, 217 p.
Keywords: Literary studies are at a tipping point. ." There is broad agreement that the discipline is in "crisis" - that it is aimless, that its intellectual energy is spent, that all of the trends are bad, and that fundamental change will be required to set things right. But there is little agreement on what those changes should be, and no one can predict which way things will ultimately tip. Literature, Science, and a New Humanities represents a bold new response to the crisis in academic literary studies. This book presents a total challenge to dominant paradigms of literary analysis and offers a sweeping critique of those paradigms, and sketches outlines of a new paradigm inspired by scientific theories, methods, and attitudes.